Voters' Preference Shift in Legislative Members Election between the 2009 Election and the 2019 Election in Kudus Regency - Eta Yuni Lestari; Nugraheni Arumsari (Political Science Program, Universitas Negeri Semarang, 2022)
The purpose of this study is to determine whether there was a shift in voter preferences between the 2009 legislative election and the 2019 legislative election in Kudus regency. The method used in this study is a qualitative method with data collection through interviews, questionnaires, and documentation studies. Previously, the author had conducted research on the 2009 legislative election and tried to develop research with the same theme in 2019. The results showed that voter preferences in the 2009 legislative election were influenced by the work program offered, giving a certain amount of money, candidate figures, relationship factors (candidates are friends, relatives, or from the same village as voters), political party preferences, religious/ideological similarity with legislative candidates, form of loyalty to legislative candidates. Political preferences in the 2019 legislative elections in Kudus Regency, however, were influenced by the vision, mission, work programs of legislative candidates, candidate figures, political parties, giving money, advertisements on social media, KPU websites, campaigns through banners and television, family influence, feeling/without being able to give reasons. There was also a shift in voter preferences between 2009 and 2019, namely the technological advances that influenced the development of political advertisements on several social media, internet, and KPU websites that were used by voters, especially novice voters in determining their political choices.